Admissibility of the Tortious Liability Action regarding the Employment Relationship - Laura Manea (Bulletin of the Transilvania University of Braşov: Series VII: Social Sciences, Law, 2022)
Tort liability is one of the important legal institutions in civil law seeking compensation for damage, and in certain circumstances, we also find it in employment relationships as a form distinct from patrimonial liability, the objective of which is also compensation for damage. Given the onerous nature of the employment relationship, in the cases that we will analyze about the admissibility of tort liability, we start from the same rights and obligations of the parties in the sense that the damage caused by the employee or the employer is due a failure in fulfilling the obligations in the employment relationship. Although the patrimonial liability as regulated by Art. 254 of the Labor Code is a special responsibility of the employment relationship, the text of the law does not qualify this type of liability as exclusive in the case of the employment relationship, which is why the case-laws identify situations where tort liability is also generated in the context of such employment relationships.